Liver Disorders A Point of Care Clinical Guide - Saeian, Kia.; Shaker, Reza.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is a comprehensive and easy-to-access guide not only in the diagnosis of the various types of liver disease but in the management of specific disorders, including the particular nuances of the care of the patient with liver disease. It provides a resource to the practitioner caring for patients with liver disease for addressing everyday questions posed by patients and their families, as well as referring physicians, in a manner that can easily be conveyed. The spectrum covered includes appropriate testing and disease monitoring of patients, use of medications, supplements, alternative therapies and alcohol, operative risk assessment, implementation of health maintenance for patients with chronic liver disease and cirrhosis, identification and management of particular complications of cirrhosis, and appropriate referral for liver transplantation, as well as management of special populations. Written by experts in the field, Liver Disorders: A Point of Care Clinical Guide is a valuable resource for clinicians who treat patients with a variety of liver disorders. .
What Do Abnormal Liver Tests Mean? -- General Care of the Liver Patient -- Do I - Need a Liver Biopsy? -- Incidental Hepatic Lesions -- Benign Hepatic Lesions -- Malignant Liver Lesions -- Health Maintenance in Liver Disease and Cirrhosis -- Pre-operative and Post-operative Care of the Liver Patient -- Viral Hepatitis: Hepatitis A & E -- Viral Hepatitis: Hepatitis B (& D) -- Viral Hepatitis: Hepatitis C -- Viral Hepatitis: Other Viral Hepatides -- Alcoholic Liver Disease -- Non-alcoholic Fatty Liver Disease -- Autoimmune Liver Diseases: Autoimmune Hepatitis -- Autoimmune Liver Diseases: Primary Biliary Cirrhosis -- Autoimmune Liver Diseases: Primary Sclerosing Cholangitis -- Autoimmune Liver Diseases: Overlap Syndromes -- Metabolic and Genetic Liver Diseases: Alpha-1 Anti-Trypsin Deficiency -- Metabolic and Genetic Liver Diseases: Hemochromatosis -- Metabolic and Genetic Liver Diseases: Wilson Disease -- Metabolic and Genetic Liver Diseases: Glycogen Storage Diseases -- Metabolic and Genetic Liver Diseases: Urea Cycle Defects -- Metabolic and Genetic Liver Diseases: Porphyrias -- Drug-Induced Liver Injury -- Miscellaneous Disorders: Pregnancy Associated Liver Disorders, Vascular Disorders, Granulomatous Disease, and Amyloidosis -- Portal Hypertension -- Endoscopic Management of Portal Hypertension -- Portosystemic Encephalopathy -- Ascites -- Spontaneous Bacterial Peritonitis (SBP) -- Hepatorenal Syndrome -- Hepatopulmonary Syndrome -- Endoscopy and the Liver Patient -- Liver Resection -- Liver Transplantation: An Overview. .
Keywords: Medicine; Gastroenterology; Hepatology; Surgical transplantation; Medicine & Public Health; Hepatology; Gastroenterology; Transplant Surgery